2006
DOI: 10.1016/j.prostaglandins.2006.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selective prostaglandins E2 receptor agonists on cultured calvarial murine osteoblastic cells

Abstract: We compared the direct effects of selective EP4 and EP2 receptor agonists (EP4A and EP2A) with prostaglandin E 2 (PGE 2 ) on the differentiation of cultured murine calvarial osteoblastic cells. EP4A increased alkaline phosphatase activity and osteocalcin mRNA levels in these cultures similar to PGE 2 . This effect was seen with both "direct plating" immediately after isolating the cells, or "indirect plating" in which the cells were grown to confluence and replated. EP2A had a smaller effect, significant only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…The greater relative effect of PGE 2 , compared to EP2A in POB cultures confirms our previous findings. The persistent effects of PGE 2 in EP2 receptor KO cells presumably reflect an effect mediated by activation of the EP4 receptor which we have shown to stimulate osteoblast differentiation and function [3,4]. A small increase in EP4 receptor mRNA expression in the EP2 KO cells suggests that this may be a compensatory mechanism that could operate in vivo and explain the absence of histologic changes in the bones of EP2 receptor KO animals.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The greater relative effect of PGE 2 , compared to EP2A in POB cultures confirms our previous findings. The persistent effects of PGE 2 in EP2 receptor KO cells presumably reflect an effect mediated by activation of the EP4 receptor which we have shown to stimulate osteoblast differentiation and function [3,4]. A small increase in EP4 receptor mRNA expression in the EP2 KO cells suggests that this may be a compensatory mechanism that could operate in vivo and explain the absence of histologic changes in the bones of EP2 receptor KO animals.…”
Section: Discussionmentioning
confidence: 69%
“…In rat calvarial organ cultures selective agonists for the EP4 and EP2 receptors (EP4A and EP2A) increased bone collagen synthesis, while agonists for EP1 and EP3 receptors as well as other prostanoids were ineffective [2,3]. In osteoblastic cells derived from neonatal mouse calvariae the effects of PGE 2 on alkaline phosphatase activity and osteocalcin gene expression could be mimicked by EP4A, while EP2A was less effective [4]. On the other hand EP2A was more effective than EP4A in increasing cAMP production in these cells [5].…”
Section: Introductionmentioning
confidence: 99%
“…PGE 2 is important in osteoblastogenesis and COX-2 inhibitors reduce measures of bone formation in vitro. [33][34][35] PGE 2 stimulates BMP-2 production by osteoblast progenitor cells 36 and COX-2 is required for both endochondral ossification and woven bone formation during fracture repair. 34,37 Our data show that COX inhibitors also impair healing of SFxs.…”
Section: Discussionmentioning
confidence: 99%
“…a. Osteoblasts. It has been shown that PGE 2 stimulates osteoblastic differentiation from bone marrow-derived cells (Shamir et al, 2004;Alander and Raisz, 2006), leading to increased osteoblast numbers and bone formation. PGE 2 also induced the expression of Runt-related transcription factor 2 (Runx2) and enhanced the formation of mineralized nodules in a culture of bone marrow cells from wildtype mice but not in a culture of cells from EP4-deficient mice (Yoshida et al, 2002).…”
Section: Other Immune Cellsmentioning
confidence: 99%
“…This positive effect of EP4 on osteoblast differentiation was supported by several subsequent pharmacological studies. Studies using EP4 agonists (ONO-AE1-329 or ONO-4819) or EP4 antagonists (L-161,982) have shown that EP4 activation induces osteoblast differentiation of murine calvarial osteoblastic cells (Alander and Raisz, 2006), rat and mouse bone marrow stromal cells (Keila et al, 2001;Shamir et al, 2004;Nakagawa et al, 2007), and the multipotent mesenchymal cell line C3H10T1/2 (Ninomiya et al, 2011).…”
Section: Other Immune Cellsmentioning
confidence: 99%